Age-wise and Gender-wise Prevalence of Hepatitis B Virus (HBV) Infection in Lahore, Pakistan - Nazeer, Aqib; Ali, Shahid; Tipu, Imran (BioScientific Review, 2019)
Background The prevalence of hepatitis B virus (HBV) in the Pakistani population has been reported previously, however, studies with a city-oriented approach and focus on age and gender distribution are very limited. Therefore, the current study was designed to unravel the age-wise and gender wise prevalence of HBV in Lahore, Pakistan. Methods A total of 350 blood samples of both male and female patients who visited National Genetic Laboratory, Lahore between February 2019 and July 2019 and who were suspected of HBV infection were screened. Sandwich based ELISA was used to detect rapid hepatitis B surface antigen (HbsAg) according to the manufacturer’s instruction. Real time PCR was used to detect HBV using HBV Rotor Gene PCR kit. Results Out of 350 blood samples screened for HBV infection (n= 350), 180 (51.43%) were of males and 170 (48.57%) were of females. Mean age (years) with SD (standard deviation) of the screened population was 37.22 ± 12.16 years. Overall, 224 samples (64%) were found to be positive for HBV infection. In our study, the number of females with this infection (52.24%) was slightly higher than males (47.76%). However, we observed no statistically significant difference (p = 0.225) between them. Conclusion Our study concludes that HBV is highly prevalent in Lahore, Pakistan. Females are slightly more susceptible to HBV infection as compared to males. This study also reports that HBV is more prevalent in the 20-40 age group.